2017
DOI: 10.1136/bmjopen-2016-015674
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, perceptions and habits towards antibiotics dispensed without medical prescription: a qualitative study of Spanish pharmacists

Abstract: ObjectiveTo investigate community pharmacists’ knowledge, attitudes, perceptions and habits with regard to antibiotic dispensing without medical prescription in Spain.MethodsA qualitative research using focus group method (FG) in Galicia (north-west Spain). FG sessions were conducted in the presence of a moderator. A topic script was developed to lead the discussions, which were audiorecorded to facilitate data interpretation and transcription. Proceedings were transcribed by an independent researcher and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
5
34
0
Order By: Relevance
“…Non-prescription (OTC) AB use and antibiotic self-medication (SMA) is one of the main factors in the irrational use of ABs and the development of MDR bacteria, so controlling AB use may present as a viable means of intervention [36][37][38]. Our results (e.g., 26% of the interviewed had dispensed non-prescribed ABs) are comparable with those found by Vazquez-Lago et al, as they found that 5%-20% of the pharmacists dispensed non-prescribed ABs [39]. A very similar proportion of the Albanian pharmacists, 89%, thought that ABs should not be given out without a prescription [35].…”
Section: Non-prescription Ab Usesupporting
confidence: 81%
See 1 more Smart Citation
“…Non-prescription (OTC) AB use and antibiotic self-medication (SMA) is one of the main factors in the irrational use of ABs and the development of MDR bacteria, so controlling AB use may present as a viable means of intervention [36][37][38]. Our results (e.g., 26% of the interviewed had dispensed non-prescribed ABs) are comparable with those found by Vazquez-Lago et al, as they found that 5%-20% of the pharmacists dispensed non-prescribed ABs [39]. A very similar proportion of the Albanian pharmacists, 89%, thought that ABs should not be given out without a prescription [35].…”
Section: Non-prescription Ab Usesupporting
confidence: 81%
“…The main reasons for the malpractice of non-prescription AB-dispensing were summarized by Vazquez-Lago et al [39]: the study group had defined reasons such as economic/patient-specific (a.: pressure from patients to have their complaints rapidly resolved; b.: fear of losing loyal customers, especially in smaller towns; c.: fear of rejection by common people with not meet expectations; and d.: pressures from pharmacy owners), internal/pharmacist-specific (bad habits during dispensing and a lack of continuous professional development) and external (indifference of physicians regarding patient follow-up, a lack of communication, no enforcement on the part of the authorities). These findings have been reinforced by several other publications [33][34][35][36][37][38][40][41][42].…”
Section: Non-prescription Ab Usementioning
confidence: 99%
“…Most of the survey participants agreed that antimicrobials might cause AMR and allergic reactions, but they ignored the risk of increasing treatment costs. A large number of studies have already shown that the community pharmacy staff's knowledge of antimicrobials is good, but the perception of the cost of antimicrobials and practices toward ASP was poor [21,[29][30][31][32]. We found that the participants' most common source of knowledge about antimicrobials was pharmacy training, which indicates that pharmacy training systems in China have improved in recent years.…”
Section: Discussionmentioning
confidence: 69%
“…Several investigations in different countries have assessed the knowledge, attitudes, and behavior of the general population and physicians regarding antibiotic use [10][11][12][13][14][15]; however, relatively few have been conducted among pharmacists [16][17][18]. To date, there is a general paucity of information in the literature on this topic among Italian community pharmacists.…”
Section: Introductionmentioning
confidence: 99%